FRI0256 ADVANCED MICROCIRCULATORY DAMAGE IS ASSOCIATED WITH INCREASED PULSE WAVE REFLECTIONS IN PATIENTS WITH SSC. (2nd June 2020) - Pagkopoulou, E.; Soulaidopoulos, S.; Triantafyllidou, E.; Katsiki, N.; Kitas, G.; Karagiannis, A.; Garyfallos, A.; Dimitroulas, T.
Abstract : Background: In systemic sclerosis (SSc), inflammation and microvascular damage are fundamental in the progressive fibrotic process. Although the presence of accelerated atherosclerosis in SSc is not as well-described as in other systemic disorders namely rheumatoid arthritis, it appears that individuals suffering from the disease are at higher risk for cardiovascular events. Nailfold Video Capillaroscopy (NVC) is a non-invasive and reproducible imaging technique of the capillary vascular bed, used in the evaluation of microvascular involvement in SSc. Previous data on the association between micro- and macrovascular damage are scarce. Objectives: The aim of this study was to examine the association between micro- and macrovascular involvement in patients with SSc. Methods: This is a cross-sectional study including consecutive SSc patients attending to a Scleroderma Outpatient Clinic between March and September 2018. All the study participants underwent NVC and the findings were classified in one of the following qualitative patterns: early, active, and late NVC pattern. Capillary's density was evaluated in the distal row of each finger, based on the number of capillaries per 1 mm and the mean capillaroscopic skin ulcer risk index (CSURI) was automatically calculated with software image analysis. Carotid intima-media thickness (cIMT) was measured in the common carotid artery bilaterally, according to the relevant guidelines. Aortic blood pressure (BP), heart rate adjusted augmentation index [AIx(75)] and carotid-femoral pulse wave velocity (PWV) were evaluated with applanation tonometry (Sphygmocor). Results: Sixty-four (95, 3% women) SSc individuals with mean age 57.54±12.99 years were included in this analysis. AIx(75) was significantly associated with CSURI (r=0.261; p=0.038) and inversely associated with the number of capillaries (r=-0.271; p=0.030) suggesting a link between the degree of microvascular disease and arterial stiffening. Regarding SSc-specific NVC patterns, AIx(75) were marginally lower in patients with early compared to active or late patterns (25.95±11.27 vs 32.50±11.17 vs 31.62±10.32%; p=0.081 and p=0.083) confirming a trend between progressive microvasculopathy and arterial stiffness. Mean cIMT was negatively correlated with enlarged capillary loops. Brachial or aortic systolic BP (SBP) and pulse pressure (PP) levels were not correlated with any of the studied NVC parameters. Conclusion: Microvascular vasculopathy is associated with higher wave reflections, indicating an association between atherosclerotic disease and microvascular injury in SSc patients. Such observations may provide possible explanations for the excessive cardiovascular and mortality risk in this population. References: [1] Soulaidopoulos, S., Pagkopoulou, E., Katsiki, N. et al. Arterial stiffness correlates with progressive nailfold capillary microscopic changes in systemic sclerosis: results from a cross-sectional study. Arthritis Res Ther 21, 253 (2019) [2] Jung K-H, Lim MJ, Kwon SR, Kim D, Joo K, Park W. Nailfold capillary microscopic changes and arterial stiffness in Korean systemic sclerosis patients. Mod Rheumatol. 2015;25:328–31. [3] Aviña-zubieta JA, Man A, Yurkovich M, Huang K, Sayre EC. Early cardiovascular disease after the diagnosis of systemic sclerosis. Am J Med. 2015;129:324–31 Disclosure of Interests: Eleni Pagkopoulou: None declared, Stergios Soulaidopoulos: None declared, Eva Triantafyllidou: None declared, Niki Katsiki: None declared, Georeg Kitas: None declared, Asterios Karagiannis: None declared, Alexandros Garyfallos Grant/research support from: MSD, Aenorasis SA, Speakers bureau: MSD, Novartis, gsk, Theodoros Dimitroulas: None declared